Soft Skills for Employment in Morocco: A Value Over or Equal to the Technical Know-how? - Ezzaidi, Mohamed (Journal of Digital Sociohumanities, 2024)
Soft skills comprise a blend of social abilities, interpersonal communication, knowledge, and character traits that enhance individuals' social and professional lives. Beyond technical expertise, soft skills are widely recognized for significantly improving employability prospects and aiding job candidates in enhancing their competitiveness during job hunting and career development. While some research projects suggest that technical knowledge is less crucial than soft skills in job interviews, other scholars argue for an equal emphasis on both to craft a comprehensive job applicant profile. This paper investigates this topic from a three-pronged perspective. First, it explores the extent to which soft skills overshadow technical knowledge in the eyes of employers in the Moroccan job market. Second, it assesses the level of engagement of Moroccan university students in learning and acquiring soft skills. Finally, it underscores the role of higher education teachers in cultivating soft skills through their instruction. This study is an exploratory endeavor that utilizes secondary data sources from scientific journals and administers questionnaires to teachers, enterprise managers, and students to unveil their attitudes in the Moroccan context. The results reveal some disparities between the existing literature and the situation in Morocco. It appears that the interest in soft skills in Morocco is still influenced more by personal and functional variables than institutional recommendations.